Effect of γ-radiation in the survival of Aspergillus parasiticus in chestnuts - Calado, Thalita (2011)
In this study, the use of rays as an inactivation agent agains one of the most ubiquous and mycotoxigenic fungus - Aspergillus parasiticus - was studied. Chestnuts were previous incoulated with a spore suspension of one strain of A. parasiticus. After irradiation the growth of colonies were observed during 4 days. In general, the higher level of radiation the lower survival rate.